2020
DOI: 10.1097/md.0000000000022095
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal fumigant and lotion for postoperative complication in surgical wound of anal fistula

Abstract: Background: Surgery is the most common and effective therapy for anal fistula, while the postoperative complication, such as pain, edema, pruritus, turgescence, and exudation in surgical wound, can have serious impact on wound healing and patients’ quality of life. Chinese herbal fumigant and lotion have been commonly used in postoperative treatment and achieved satisfied effect in China. However, clinical evidence-based literature of Chinese herbal fumigant and lotion for postoperative anal fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Previous scholars have used iodophor, infrared radiation, potassium permanganate, and other methods for treatment of anal fistula, but the effect is not ideal [ 16 ]. Studies by [ 17 ] utilizing the Chinese herbal fumigant with lotion for curing postoperative wounds in anal fistula with results showing great efficacy. Zhang et al [ 14 ] showed that Chinese medicine helps patients recover faster and has fewer side effects than Western medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Previous scholars have used iodophor, infrared radiation, potassium permanganate, and other methods for treatment of anal fistula, but the effect is not ideal [ 16 ]. Studies by [ 17 ] utilizing the Chinese herbal fumigant with lotion for curing postoperative wounds in anal fistula with results showing great efficacy. Zhang et al [ 14 ] showed that Chinese medicine helps patients recover faster and has fewer side effects than Western medicines.…”
Section: Introductionmentioning
confidence: 99%
“…However, diabetic patients with large wounds after anal fistula surgery have an increased probability of wound infection, accompanied by pain, itching, swelling, and exudation, which are not easy to heal. Therefore, it is particularly important to shorten the wound healing time ( Yang et al, 2017 ; Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the perianal skin is tender, and the anal pain nerve is rich. Moreover, due to the need for defecation every day, the postoperative wound is not only polluted by feces, but also the mechanical damage in the defecation process will aggravate the trauma of the postoperative wound of anal stula, resulting in the slow healing of the postoperative wound of anal stula, which seriously affects the rest, eating and activity of patients, thereby affecting the postoperative recovery [8,9]. How to promote wound healing after anal stula surgery has become an important issue for clinicians.…”
Section: Discussion and 41 Research Status Shengji Yuhong Ointmentmentioning
confidence: 99%